RANCANG BANGUN MESIN PENGGEMBUR TANAH MENGGUNAKAN MATA BAJAK TIPE CANGKUL DENGAN KEMIRINGAN SUDUT 110° - Filgantara, Yuda; Saparin, Saparin; Setiawan, Yudi; Wijianti, Eka Sari; Ariksa, Jeri (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Indonesia is an agricultural country where the majority of the population is farming. Farmers in Indonesia still use many traditional methods in processing agricultural land such as using hoes. In previous studies, a soil bulking machine was made with a slope of the plow blade angle of 90 ° and obtained less than optimal loose results. The influencing factor is that the angle of the hoe eye is not large, therefore the manufacture of a soil bulking machine is carried out using a hoe-shaped plow with the slope of the corner of the hoe eye enlarged to 110 °. The soil bulking machine uses 30 hoe-shaped plowshares with a hoe blade height of 10 cm, a width of 10 cm and a hoe tip thickness of 6 mm. The type of soil that can be plowed by this soil bulking machine is soil that has been cultivated on agricultural land. The test was conducted on an area of 28 m2. In the first experiment, it took an average of 18.78 seconds with an average pirated depth of 9.76 cm. In the second experiment, it took an average of 16.91 seconds with an average pirated depth of 9.30 cm. In the third experiment, it took an average of 19.24 seconds with an average pirated depth of 11.26 cm. The result of soil loosening with an average productivity of 1.53 m2 / second with an average depth of 10.10 cm.